High-density electric composite pipe and preparation method thereof
By using polypropylene-polyethylene mixed materials and boron nitride and other components in composite pipes, high-density power composite pipes are prepared, which solves the problem of insufficient impact resistance and thermal stability of existing composite pipes, and achieves higher mechanical properties and connection performance.
Patent Information
- Application Number
- CN202411951309.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Existing composite pipes have shortcomings in impact resistance and thermal stability, which limits their application in engineering plastics.
Polypropylene-polyethylene mixed material is used as the base material, and boron nitride, epoxy resin composite material, white carbon black and styrene butadiene rubber are added to prepare high-density power composite pipes through blending and extrusion molding technology.
It significantly improves the impact resistance and thermal stability of composite pipes, improves the mechanical properties and connection properties of the materials, and is suitable for high-performance engineering plastic applications.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of composite pipes, and in particular to a high-density electric composite pipe and a preparation method thereof. Background Art
[0002] Pipes are construction materials that can be used for transportation. Composite pipes are pipes based on thermoplastic composite structures. They are lined with plastic polypropylene, polyethylene or welded cross-linked polyethylene and other non-metallic materials. They are widely used in the power industry.
[0003] Polypropylene has good heat resistance, mechanical properties, electrical insulation, low cost, easy processing and as a thermoplastic polymer, it is easy to recycle and reuse. It can be used as the matrix of composite thermal conductive polymer materials. However, due to the low impact strength of polypropylene, its wide application in engineering plastics is limited. Summary of the invention
[0004] In order to further improve the comprehensive performance of composite pipes, the present application provides a high-density electric composite pipe and a preparation method thereof.
[0005] The present application provides a high-density electric composite pipe and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides a high-density electric composite pipe, which adopts the following technical solution: A high-density electric composite pipe comprises a polypropylene layer and a polyolefin composite layer, wherein the polyolefin composite layer comprises the following components by weight: 107-140 parts of polypropylene-polyethylene mixed material, 42-52 parts of epoxy resin composite material, 12-18 parts of white carbon black, 20-26 parts of styrene-butadiene rubber, 7-9 parts of plasticizer, and 4-6 parts of dispersant; The polypropylene-polyethylene mixed material comprises polypropylene, high-density polyethylene, boron nitride and polypropylene grafted with maleic anhydride.
[0006] By adopting the above technical scheme, polypropylene, high-density polyethylene, boron nitride and polypropylene grafted maleic anhydride are mixed to prepare a polypropylene-polyethylene mixed material. Polypropylene, as the base material of the composite pipe, has good heat resistance and mechanical properties, and is easy to process. However, the impact strength of the polypropylene material is weak. After adding high-density polyethylene, the overall impact resistance of the system can be effectively improved. Boron nitride has good thermal conductivity, oxidation resistance, corrosion resistance and chemical stability. After adding, it can effectively improve the thermal conductivity at the interface of the substrate, thereby improving the overall thermal stability of the pipe. Polypropylene grafted maleic anhydride enhances the compatibility between polypropylene and boron nitride in the composite material, allowing more particles to enter the polypropylene, promoting the nucleation effect of boron nitride in polypropylene, and further improving the stability of the system. The pipe is also added with an epoxy resin composite material, which has good connection performance, so that the material bonding performance in the pipe is improved, and the mechanical properties of the pipe can be further improved.
[0007] Preferably, the mass ratio of the polypropylene, high-density polyethylene, boron nitride and polypropylene grafted maleic anhydride is 64:16:15:(5.3-5.7).
[0008] By adopting the above technical solution, the mass ratio of polypropylene, high-density polyethylene, boron nitride and polypropylene grafted maleic anhydride is preferably within the above range, and the boron nitride is dispersed in the matrix similar to a sea-island structure, which can further improve the comprehensive performance of the polypropylene-polyethylene hybrid material.
[0009] Preferably, the epoxy resin composite material comprises modified carboxyl carbon nanotubes, composite aramid fibers, epoxy resin and tannic acid.
[0010] By adopting the above technical solution, epoxy resin added to the pipe can effectively improve the connection performance between the various components in the pipe. Modified carboxyl carbon nanotubes, composite aramid fibers, etc. are added to the epoxy resin to fill the gaps between the materials, so that the surface area per unit volume is increased, thereby improving the bonding force between the interfaces. Carbon nanotubes have excellent mechanical properties, thermal properties, electrical properties, and high specific surface area. After being added to the system, stress can be better transferred to the material, while improving the overall heat resistance of the system. However, in the strong van der Waals force and π-π bond Under the interaction of carbon nanotubes, carbon nanotubes have a very high cohesive force. The modified carbon nanotubes can improve their agglomeration phenomenon and enhance the dispersion performance of carbon nanotubes, thereby improving the stability of the prepared epoxy resin composite material; aramid fibers can enhance the connection relationship between the components in the system, further making the connections between the components in the system closer; tannic acid, as a renewable resource, can be introduced into the system to modify the epoxy resin, so as to further enhance the cross-linking and bonding properties of the epoxy resin, thereby improving the comprehensive performance of the prepared epoxy resin composite material.
[0011] Preferably, the modified carboxyl carbon nanotubes are prepared by the following method: The polyethyleneimine is mixed with water to obtain a polyethyleneimine aqueous solution, the carboxylated multi-walled carbon nanotubes are added to the polyethyleneimine aqueous solution, condensed and refluxed, vacuum filtered, washed and freeze-dried to obtain modified carboxyl carbon nanotubes.
[0012] By adopting the above technical scheme, polyethyleneimine is grafted onto the surface of carboxylated multi-walled carbon nanotubes through an amidation reaction. The high molecular weight polyethyleneimine grafted on the surface of the carbon nanotubes can effectively improve the dispersion effect of the carbon nanotubes in the epoxy resin, and can participate in a part of the subsequent curing and cross-linking reaction of the epoxy resin, thereby improving the interface bonding between the carbon nanotubes and the epoxy resin body, thereby improving the comprehensive performance of the epoxy resin composite material.
[0013] Preferably, the mass ratio of the carboxyl carbon nanotubes to polyethyleneimine is (0.08-0.12):1.
[0014] By adopting the above technical solution, preferably the mass ratio between the carboxyl carbon nanotubes and the polyethyleneimine is within the above range, the comprehensive performance of the prepared modified carboxyl carbon nanotubes can be effectively improved.
[0015] Preferably, the composite aramid fiber is prepared by the following method: Glycidyl polyhedral silsesquioxane, polyamic acid and tetrahydrofuran are mixed to obtain a mixed solution; aramid fiber is added to the mixed solution, taken out after immersion, and placed in a supercritical CO2 reactor, the aramid fiber is taken out after treatment, and then heated to obtain a composite aramid fiber.
[0016] By adopting the above technical scheme, aramid fibers are modified with the assistance of small molecule glycidyl polyhedral silsesquioxane and macromolecular polyamic acid with the aid of supercritical CO2, which can effectively improve the bonding performance between aramid fibers and other components. At the same time, the interfacial twisting properties of styrene-butadiene rubber can also be further enhanced, thereby improving the overall mechanical properties of the composite material.
[0017] Preferably, the mass concentration of glycidyl polyhedral silsesquioxane in the mixed solution is 4-6%, and the concentration of polyamic acid is 4-6%.
[0018] By adopting the above technical solution, the concentrations of glycidyl polyhedral silsesquioxane and polyamic acid in the mixed solution are preferably within the above range, which can further improve the comprehensive performance of the prepared composite aramid fiber.
[0019] Preferably, the epoxy resin composite material is prepared by the following method: Tetraglycidyl-4,4'-diaminodiphenylmethane is mixed with acetone, and then tannic acid is added, and the solvent is evaporated by heating and stirring, and then m-phenylenediamine is added to obtain a mixture, and the mixture is vacuumed to remove bubbles to obtain a modified epoxy resin; the modified epoxy resin, composite aramid fiber and modified carboxyl carbon nanotubes are mixed and stirred to obtain an epoxy resin composite material.
[0020] By adopting the above technical scheme, tannic acid is used to toughen and modify epoxy resin. Tannic acid has a special highly branched spherical structure and a large number of active phenolic hydroxyl groups, which can act as a physical-chemical crosslinking point, promote the curing and crosslinking reaction of epoxy resin, and improve the interfacial interaction of the body. At the same time, it can improve the crosslinking density, further improve the overall tensile strength and elongation at break of the epoxy resin composite material, so that the comprehensive performance of the prepared composite pipe is improved.
[0021] Preferably, the mass ratio of the modified carboxyl carbon nanotubes, aramid fibers and modified epoxy resin is (0.05-0.09):1:5.6.
[0022] By adopting the above technical solution, the mass ratio of the modified carboxyl carbon nanotubes, the aramid fiber and the modified epoxy resin is preferably within the above range, which can further improve the comprehensive performance of the prepared epoxy composite material.
[0023] In a second aspect, the present application provides a method for preparing a high-density electric composite pipe, which adopts the following technical solution: The method for preparing a high-strength electric composite pipe comprises the following steps: The polypropylene-polyethylene mixed material, white carbon black, styrene-butadiene rubber, plasticizer, and dispersant are added to an internal mixer for internal mixing, and then the internal mixed material and the epoxy resin composite material are added to a twin-screw extruder to form a polyolefin composite layer, and co-extruded with the polypropylene layer used to be prepared in the twin-screw extruder to obtain an electric composite pipe. In summary, the present application includes at least one of the following beneficial technical effects: The composite pipe prepared in the present application is added with a polypropylene-polyethylene composite prepared by polypropylene, high-density polyethylene, boron nitride and polypropylene grafted maleic anhydride. After the polypropylene and high-density polyethylene are mixed, the overall impact resistance of the system can be improved by compounding. Boron nitride has good thermal conductivity, oxidation resistance, corrosion resistance and chemical stability. Adding it to the system can effectively improve the thermal conductivity at the interface of the substrate, so that the thermal stability of the composite pipe is improved. Polypropylene grafted maleic anhydride enhances the compatibility between polypropylene and boron nitride, allowing more particles to enter the polypropylene, promoting the nucleation effect of boron nitride in polypropylene, thereby further improving the stability of the system. Epoxy resin composite material, white carbon black and styrene-butadiene rubber are also added to the pipe, which can effectively improve the mechanical properties of the composite pipe; The epoxy resin composite material is prepared by modified carboxyl carbon nanotubes, composite aramid fibers, epoxy resin and tannic acid. The modified carboxyl carbon nanotubes and composite aramid fibers can be filled into the gaps between the epoxy resin materials to enhance the bonding force between the interfaces, thereby improving the mechanical properties of the epoxy resin. Tannic acid is introduced into the system to modify the epoxy resin, further enhancing the crosslinking performance and adhesion of the epoxy resin, so that the comprehensive performance of the epoxy resin composite material is improved. The modification of aramid fibers with the assistance of small molecule glycidyl polyhedral silsesquioxane and macromolecular polyamic acid with supercritical CO2 can effectively improve the bonding performance between aramid fibers and other components. At the same time, the interfacial adhesion to styrene-butadiene rubber can be further enhanced, thereby improving the overall mechanical properties of the composite material. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained commercially; Example 1
[0025] Preparation of polypropylene-polyethylene blends: 127.62 g of polypropylene, 31.9 g of high-density polyethylene, 29.91 g of boron nitride and 10.57 g of polypropylene grafted maleic anhydride were dried in an oven at 50° C. for 6 h, respectively. The dried raw materials were then mixed in a mixer for 3 min, melted, blended and extruded through a screw extruder to obtain a polypropylene-polyethylene mixed material, wherein the four zone temperatures of the screw extruder were 160° C., 175° C., 185° C. and 170° C., respectively, and the screw speed was 15 r / min.
[0026] Preparation of modified carboxyl carbon nanotubes: 0.37 g of polyethyleneimine was added to 100 mL of deionized water to obtain a polyethyleneimine aqueous solution, and 4.63 g of carboxylated multi-walled carbon nanotubes were added to the polyethyleneimine aqueous solution. The mixture was condensed and refluxed at 120° C. for 12 h, vacuum filtered, and then repeatedly washed with deionized water for 5 times. The mixture was freeze-dried in a hollow freezer at -20° C. for 12 h to obtain modified carboxyl carbon nanotubes.
[0027] Preparation of composite aramid fibers: Glycidyl polyhedral silsesquioxane, polyamic acid and tetrahydrofuran are mixed to obtain 200 mL of a mixed solution, in which the mass concentration of glycidyl polyhedral silsesquioxane is 4%, and the mass concentration of polyamic acid is 6%. 20 g of aramid fiber with a length of 2 mm is added to the above mixed solution and immersed for 10 minutes. The aramid fiber is then taken out and placed in a supercritical CO2 reactor and treated at 50°C and 10 MPa for 30 minutes. The aramid fiber is then taken out and heated to 250°C for 2 hours to obtain a composite aramid fiber.
[0028] Preparation of epoxy resin composites: 80 g of tetraglycidyl-4,4'-diaminodiphenylmethane was mixed with 500 g of acetone, and then 2.4 g of tannic acid was added. The temperature was raised to 80° C. and stirred to evaporate the solvent. Subsequently, 110 g of m-phenylenediamine was added, and the mixture was heated at 80° C. to dissolve all the components. The bubbles were removed by vacuum drying in a vacuum drying oven to obtain a modified epoxy resin. 66.96 g of the modified epoxy resin, 11.96 g of the composite aramid fiber and 1.08 g of the modified carboxyl carbon nanotubes were mixed and stirred at a speed of 200 r / min for 20 min to obtain an epoxy resin composite material.
[0029] Preparation of power composite pipes: 107 g of polypropylene-polyethylene mixed material, 12 g of white carbon black, 20 g of styrene-butadiene rubber, 7 g of plasticizer and 4 g of dispersant are mixed to obtain a mixture, and the mixture is added to an internal mixer and mixed at 170°C for 20 min. Subsequently, the mixed material and 42 g of epoxy resin composite material are added to a twin-screw extruder, the temperature of each zone of the twin-screw extruder is 200°C, the screw speed is 170 r / min, and the material is co-extruded with the polypropylene material in the twin-screw extruder to obtain an electric composite pipe having a polypropylene layer and a polyolefin composite layer. Example 2
[0030] Preparation of polypropylene-polyethylene blends: 127.11 g of polypropylene, 31.78 g of high-density polyethylene, 29.79 g of boron nitride and 11.32 g of polypropylene grafted maleic anhydride were dried in an oven at 50°C for 6 hours, respectively. The dried raw materials were then mixed in a mixer for 3 minutes, melted, blended and extruded through a screw extruder to obtain a polypropylene-polyethylene mixed material, wherein the four zone temperatures of the screw extruder were 160°C, 175°C, 185°C and 170°C, respectively, and the screw speed was 15 r / min.
[0031] Preparation of modified carboxyl carbon nanotubes: 0.54 g of polyethyleneimine was added to 100 mL of deionized water to obtain a polyethyleneimine aqueous solution, and 4.46 g of carboxylated multi-walled carbon nanotubes were added to the polyethyleneimine aqueous solution. The mixture was condensed and refluxed at 120° C. for 12 h, vacuum filtered, and then repeatedly washed with deionized water for 5 times. The mixture was freeze-dried in a hollow freezer at -20° C. for 12 h to obtain modified carboxyl carbon nanotubes.
[0032] Preparation of composite aramid fibers: Glycidyl polyhedral silsesquioxane, polyamic acid and tetrahydrofuran are mixed to obtain 200 mL of a mixed solution, in which the mass concentration of glycidyl polyhedral silsesquioxane is 6%, and the mass concentration of polyamic acid is 4%. 20 g of aramid fiber with a length of 2 mm is added to the above mixed solution and immersed for 10 minutes. The aramid fiber is then taken out and placed in a supercritical CO2 reactor and treated at 50°C and 10 MPa for 30 minutes. The aramid fiber is then taken out and heated to 250°C for 2 hours to obtain a composite aramid fiber.
[0033] Preparation of epoxy resin composites: 80 g of tetraglycidyl-4,4'-diaminodiphenylmethane was mixed with 500 g of acetone, and then 2.4 g of tannic acid was added. The temperature was raised to 80°C and stirred to evaporate the solvent. Subsequently, 110 g of m-phenylenediamine was added, and the mixture was heated at 80°C to dissolve all the components. The bubbles were removed by vacuum drying in a vacuum drying oven to obtain a modified epoxy resin. 66.77 g of the modified epoxy resin, 11.92 g of the composite aramid fiber and 1.31 g of the modified carboxyl carbon nanotubes were mixed and stirred at a speed of 200 r / min for 20 minutes to obtain an epoxy resin composite material.
[0034] Preparation of power composite pipes: 140 g of polypropylene-polyethylene mixed material, 18 g of white carbon black, 26 g of styrene-butadiene rubber, 9 g of plasticizer and 6 g of dispersant were mixed to obtain a mixture, which was added to an internal mixer and mixed at 170°C for 20 min. Subsequently, the mixed material and 52 g of epoxy resin composite material were added to a twin-screw extruder, the temperature of each zone of the twin-screw extruder was 200°C, the screw speed was 170 r / min, and the material was co-extruded with the polypropylene material in the twin-screw extruder to obtain an electric composite pipe having a polypropylene layer and a polyolefin composite layer. Example 3
[0035] Preparation of polypropylene-polyethylene blends: 127.36 g of polypropylene, 31.84 g of high-density polyethylene, 29.85 g of boron nitride and 10.95 g of polypropylene grafted maleic anhydride were dried in an oven at 50° C. for 6 h, respectively. The dried raw materials were then mixed in a mixer for 3 min, melted, blended and extruded through a screw extruder to obtain a polypropylene-polyethylene mixed material, wherein the four zone temperatures of the screw extruder were 160° C., 175° C., 185° C. and 170° C., respectively, and the screw speed was 15 r / min.
[0036] Preparation of modified carboxyl carbon nanotubes: 0.45 g of polyethyleneimine was added to 100 mL of deionized water to obtain a polyethyleneimine aqueous solution, and 4.55 g of carboxylated multi-walled carbon nanotubes were added to the polyethyleneimine aqueous solution. The mixture was condensed and refluxed at 120° C. for 12 h, vacuum filtered, and then repeatedly washed with deionized water for 5 times. The mixture was freeze-dried in a hollow freezer at -20° C. for 12 h to obtain modified carboxyl carbon nanotubes.
[0037] Preparation of composite aramid fibers: Glycidyl polyhedral silsesquioxane, polyamic acid and tetrahydrofuran are mixed to obtain 200 mL of a mixed solution, in which the mass concentration of glycidyl polyhedral silsesquioxane is 5%, and the mass concentration of polyamic acid is 5%; 20 g of aramid fiber with a length of 2 mm is added to the above mixed solution and immersed for 10 minutes, then the aramid fiber is taken out and put into a supercritical CO2 reactor, and treated for 30 minutes at 50°C and 10 MPa, then the aramid fiber is taken out and heated to 250°C for 2 hours to obtain a composite aramid fiber.
[0038] Preparation of epoxy resin composites: 80 g of tetraglycidyl-4,4'-diaminodiphenylmethane was mixed with 500 g of acetone, and then 2.4 g of tannic acid was added. The temperature was raised to 80°C and stirred to evaporate the solvent. Subsequently, 110 g of m-phenylenediamine was added, and the mixture was heated at 80°C to dissolve all the components. The bubbles were removed by vacuum drying in a vacuum drying oven to obtain a modified epoxy resin. 66.87 g of the modified epoxy resin, 11.94 g of the composite aramid fiber and 1.19 g of the modified carboxyl carbon nanotubes were mixed and stirred at a speed of 200 r / min for 20 minutes to obtain an epoxy resin composite material.
[0039] Preparation of power composite pipes: 123 g of polypropylene-polyethylene mixed material, 15 g of white carbon black, 23 g of styrene-butadiene rubber, 8 g of plasticizer and 5 g of dispersant were mixed to obtain a mixture, which was added to an internal mixer and mixed at 170°C for 20 min. Subsequently, the mixed material and 15 g of epoxy resin composite material were added to a twin-screw extruder with the temperature of each zone of the twin-screw extruder being 200°C and the screw speed being 170 r / min. The material was co-extruded with the polypropylene material in the twin-screw extruder to obtain an electric composite pipe having a polypropylene layer and a polyolefin composite layer. Example 4
[0040] Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing the composite aramid fiber, the mass concentration of glycidyl polyhedral silsesquioxane in the mixed solution is 3%, and the mass concentration of polyamic acid is 8%. Example 5
[0041] Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing the composite aramid fiber, the mass concentration of glycidyl polyhedral silsesquioxane in the mixed solution is 8%, and the mass concentration of polyamic acid is 3%. Example 6
[0042] Example 6 is based on Example 3. The difference between Example 6 and Example 5 is that only glycidyl polyhedral silsesquioxane is used to modify the aramid fiber. Example 7
[0043] Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that only polyamic acid is used to modify the aramid fiber. Example 8
[0044] Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that the composite aramid fiber in the epoxy resin composite material is not prepared by supercritical CO2. Example 9
[0045] Example 9 uses Example 3 as the base station. The difference between Example 9 and Example 3 is that when preparing the modified carboxyl carbon nanotubes, 0.24 g of polyethyleneimine and 4.76 g of carboxyl carbon nanotubes are used. Example 10
[0046] Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that when preparing the modified carboxyl carbon nanotubes, 0.65 g of polyethyleneimine and 4.35 g of carboxyl carbon nanotubes are used. Embodiment 11
[0047] Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that the modified carboxyl carbon nanotubes in the epoxy resin composite material are replaced with ordinary carbon nanotubes. Example 12
[0048] Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that when preparing the epoxy resin composite material, 0.6 g of modified carboxyl carbon nanotubes, 12.03 g of composite aramid fibers, and 67.37 g of modified epoxy resin are used. Embodiment 13
[0049] Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that when preparing the epoxy resin composite material, 1.78 g of modified carboxyl carbon nanotubes, 11.85 g of composite aramid fibers, and 66.37 g of modified epoxy resin are used. Embodiment 14
[0050] Example 14 is based on Example 3. In Example 14, no modified carboxyl carbon nanotubes are added to the epoxy resin composite material, and the modified carboxyl carbon nanotubes are replaced by composite aramid fibers of equal mass. Embodiment 15
[0051] Example 15 is based on Example 3. In Example 15, no composite aramid fiber is added to the epoxy resin composite material, and the composite aramid fiber is replaced by an equal mass of modified carboxyl carbon nanotubes. Example 16
[0052] Example 16 is based on Example 3. In Example 16, when preparing the polypropylene-polyethylene mixed material, the amount of polypropylene used is 128g, the amount of high-density polyethylene used is 32g, the amount of boron nitride used is 30g, and the amount of polypropylene grafted maleic anhydride used is 10g. Embodiment 17
[0053] Example 17 is based on Example 3. In Example 17, when preparing the polypropylene-polyethylene mixed material, the amount of polypropylene used is 126.73g, the amount of high-density polyethylene used is 31.68g, the amount of boron nitride used is 29.7g, and the amount of polypropylene grafted maleic anhydride used is 11.89g.
[0054] Comparative Example 1 In Comparative Example 1, when preparing the polypropylene-polyethylene mixed material, no polypropylene grafted maleic anhydride was added, and an equal amount of polypropylene was used instead.
[0055] Comparative Example 2 In Comparative Example 2, when preparing the polypropylene-polyethylene mixed material, no boron nitride was added, and an equal amount of polypropylene was used instead.
[0056] Comparative Example 3 In Comparative Example 3, the polypropylene-polyethylene mixed material is prepared by mixing only polypropylene and high-density polyethylene, and polypropylene is used to replace polypropylene grafted with maleic anhydride and boron nitride in equal amounts.
[0057] Performance testing The following performance tests were performed on the sample pipes of Examples 1-17 and Comparative Examples 1-3: (1) Tensile properties Taking GB / T 1040-2006 as the testing standard, the tensile properties and elongation at break of the samples were tested using a KJ-1065 high-precision peel force and release force testing machine. Each sample was tested 3 times, the average value was taken, and the test results were filled in Table 1. (2) Bending performance test The bending properties of the samples were tested according to GB / T 9341-2008. Each sample was tested 3 times, and the average value was taken. The test results were filled in Table 1. Table 1 Performance test results of Examples 1-17 and Comparative Examples 1-3
[0058] Combined with Table 1, it can be seen that the tensile strength of Examples 1-3 is 123 MPa or more, and the elongation at break is 3% or more, indicating that the composite pipe prepared by the present application has good tensile properties; the bending strength of Examples 1-3 is 130 MPa or more, indicating that the composite pipe prepared by the applicant has good bending properties.
[0059] In Example 4 and Example 5, when preparing the composite aramid fiber, the concentrations of glycidol polyhedral silsesquioxane and polyamic acid in the mixed solution are not within the range specified in the present application. When the concentration of glycidol polyhedral silsesquioxane is too small, it is difficult to promote the modification of the aramid fiber, making it difficult to further improve the bonding performance between the aramid fiber and the epoxy resin. At the same time, it is difficult to form a stable cross-linked network with the styrene-butadiene rubber, affecting the overall performance of the system; when the concentration of glycidol polyhedral silsesquioxane is too large, it self-polymerizes on the surface of the aramid fiber under the assisted penetration of supercritical CO2, and the rigidity of the fiber is improved, but the cross-linking density decreases, which also affects the performance of the system; when the concentration of polyamic acid is too small, it is difficult to further promote the cross-linking performance of the aramid fiber, and the compatibility of the aramid fiber in the system is difficult to further improve. When the concentration of polyamic acid is too large, it has a certain negative impact on the stability of the system, so the performance of Example 4 and Example 5 are both reduced.
[0060] In both Example 6 and Example 7, only a single pair of aramid fibers are modified. It is difficult for a single modified aramid fiber to synergistically promote the compatibility and cross-linking performance of the aramid fiber. Therefore, the performance of both Example 6 and Example 7 is reduced.
[0061] In Example 8, there is no supercritical CO2 assistance, and the interface connection performance is difficult to be further improved, so that the cross-linking performance of the aramid fiber is difficult to be improved, and thus the performance in Example 8 is reduced.
[0062] In Examples 9 and 10, when preparing modified carboxyl carbon nanotubes, the mass ratio between polyethyleneimine and carboxyl carbon nanotubes is not within the range specified in the present application. When the content of polyethyleneimine is too little, it is difficult to further destroy the agglomeration effect on the surface of the carboxyl carbon nanotubes, and it is difficult to form hydrogen bonds with other amino groups, and it is difficult to further form stronger interfacial interactions, which affects the performance of the system; when the content of polyethyleneimine is too much, it is difficult to further modify the carboxyl carbon nanotubes, and it will affect the overall stability of the system. Therefore, the performance of Examples 9 and 10 is reduced.
[0063] In Example 11, the epoxy resin composite material replaces the modified carboxyl carbon nanotubes with ordinary carboxyl carbon nanotubes. The dispersibility of the unmodified carboxyl carbon nanotubes is difficult to be further improved. At the same time, the compatibility of the carboxyl carbon nanotubes in the system is also difficult to be improved, which affects the overall stability of the system. Therefore, the performance of Example 11 is reduced.
[0064] In Example 12 and Example 13, when preparing epoxy resin composite materials, the mass ratios of modified carboxyl carbon nanotubes, composite aramid fibers and modified epoxy resin are not within the range specified in the present application. When the amount of modified carboxyl carbon nanotubes used is too small, it is difficult to form a stable structure between a sufficient amount of nanoparticles and the epoxy resin matrix, and the effect of the three-dimensional network structure connected in the form of covalent bonds after the system is cured is weakened, and it is difficult to improve the buffering effect. Therefore, it is difficult to further improve the mechanical properties of the system. When the content of modified carboxyl carbon nanotubes is too much, due to the high viscosity of the epoxy resin system, excessive modified carboxyl carbon nanotubes agglomerate. Under the action of external force, the performance of the composite material decreases due to stress concentration. Therefore, the performance of Example 12 and Example 13 are both reduced.
[0065] In Example 14, no modified carboxyl carbon nanotubes were added to the epoxy resin composite material. The system without modified carboxyl carbon nanotubes could not further increase the interfacial area of the epoxy resin matrix, and the performance of the system was reduced. Therefore, the performance of Example 14 was reduced.
[0066] In Example 15, no composite aramid fiber is added to the epoxy resin composite material. Without the addition of composite aramid fiber, it is difficult to further combine the components in the system, and an interlocking effect cannot be formed. The interfacial bonding force between the systems is difficult to further improve. Therefore, the performance of Example 15 is reduced.
[0067] In Example 16 and Example 17, when preparing polypropylene-polyethylene hybrid materials, the mass ratios of polypropylene, high-density polyethylene, boron nitride and polypropylene grafted maleic anhydride are not within the range specified in the present application. When the content of polypropylene grafted maleic anhydride is too little, it is difficult to further improve the overall thermal conductivity of the system, so that the interfacial compatibility of the composite material is difficult to improve, and the stability of the system is difficult to further improve, affecting the performance of the system; when the content of polypropylene grafted maleic anhydride is too much, it affects the crystallinity of the polypropylene and also affects the overall stability of the system. Therefore, the performance of Example 16 and Example 17 is reduced.
[0068] In Comparative Example 1, no polypropylene grafted maleic anhydride was added, which made it difficult to improve the compatibility between boron nitride and substrates such as polypropylene and high-density polyethylene, thereby affecting the overall performance of the system.
[0069] In Comparative Example 2, no boron nitride was added, and the gaps between the materials were difficult to be further filled, making it difficult to further improve the connection performance between the substrates, thus affecting the performance of the system.
[0070] In Comparative Example 3, only polypropylene and high-density polyethylene are mixed to prepare a polypropylene-polyethylene mixed material, and the interface compatibility and thermal stability are difficult to be further enhanced and improved, which affects the overall performance of the system, so the performance of Comparative Example 3 decreases.
[0071] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A high-density electric composite pipe, characterized by: It comprises a polypropylene layer and a polyolefin composite layer, wherein the polyolefin composite layer comprises the following components by mass: 107-140 parts of polypropylene-polyethylene mixed material, 42-52 parts of epoxy resin composite material, 12-18 parts of white carbon black, 20-26 parts of styrene-butadiene rubber, 7-9 parts of plasticizer, and 4-6 parts of dispersant; The polypropylene-polyethylene mixed material comprises polypropylene, high-density polyethylene, boron nitride and maleic anhydride.
2. The high-density electric composite pipe according to claim 1, characterized in that: The mass ratio of the polypropylene, high-density polyethylene, boron nitride and maleic anhydride is 64:16:15:(5.3-5.7).
3. The high-density electric composite pipe according to claim 1, characterized in that: The epoxy resin composite material comprises modified carboxyl carbon nanotubes, composite aramid fibers, epoxy resin and tannic acid.
4. The high-density electric composite pipe according to claim 3 is characterized in that: The modified carboxyl carbon nanotubes are prepared by the following method: The polyethyleneimine is mixed with water to obtain a polyethyleneimine aqueous solution, the carboxylated multi-walled carbon nanotubes are added to the polyethyleneimine aqueous solution, condensed and refluxed, vacuum filtered, washed and freeze-dried to obtain modified carboxyl carbon nanotubes.
5. The high-density electric composite pipe according to claim 4, characterized in that: The mass ratio of the carboxyl carbon nanotubes to polyethyleneimine is (0.08-0.12):
1.
6. The high-density electric composite pipe according to claim 3, characterized in that: The composite aramid fiber is prepared by the following method: Glycidyl polyhedral silsesquioxane, polyamic acid and tetrahydrofuran are mixed to obtain a mixed solution; aramid fiber is added to the mixed solution, taken out after immersion, and placed in a supercritical CO2 reactor, the aramid fiber is taken out after treatment, and then heated to obtain a composite aramid fiber.
7. The high-density electric composite pipe according to claim 6, characterized in that: The mass concentration of glycidyl polyhedral silsesquioxane in the mixed solution is 4-6%, and the mass concentration of polyamic acid is 4-6%.
8. The high-density electric composite pipe according to claim 3, characterized in that: The epoxy resin composite material is prepared by the following method: Tetraglycidyl-4,4'-diaminodiphenylmethane is mixed with acetone, tannic acid is added, the solvent is evaporated by heating and stirring, and then metaphenylenediamine is added to obtain a mixture, and the mixture is evacuated to remove bubbles, thereby obtaining a modified epoxy resin; The modified epoxy resin, the composite aramid fiber and the modified carboxyl carbon nanotubes are mixed and stirred to obtain an epoxy resin composite material.
9. The high-density electric composite pipe according to claim 8, characterized in that: The mass ratio of the modified carboxyl carbon nanotubes, aramid fibers and modified epoxy resin is (0.05-0.09):1:5.
6.
10. A method for preparing a high-density electric composite pipe according to any one of claims 1 to 9, characterized in that: The steps include: The polypropylene-polyethylene mixed material, white carbon black, styrene-butadiene rubber, plasticizer and dispersant are added to an internal mixer for internal mixing. Subsequently, the internal mixed material and the epoxy resin composite material are added to a twin-screw extruder to make a polyolefin composite layer, and co-extruded with the polypropylene layer made in the twin-screw extruder to obtain an electric composite pipe.
Citation Information
Patent Citations
Fiber reinforced functionalized polyolefin composites
CA2127015A1
High-toughness high-modulus polypropylene composite material and preparation method thereof
CN104592632A
Wear-resistant composite plastic for shells of mobile phones
CN106084658A
Aromatic polycarbonate resin composition, method for producing the resin composition and molded product of the resin composition
JP2006083195A